PENGARUH NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSET (ROA) PADA PT BANK NEGARA INDONESIA (PERSERO) TBK PERIODE 2011-2015 - JUWANDA, HADI; RIDO, ACEP (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2017)
This study aimed to find out the influence to non performing loan (npl) to return on asset (roa) at  PT Bank Negara Indonesia (Persero) tbk period of 2011-2015. The method used in this research was descriptive through quantitative approach. The analysis technique used is Normality Test, Simple Linear Regression, Pearson product moment correlation coefficient and coefficient of determination. Results of simple linear regression analysis was Y = 39,702 + -1,468X which meant that if the NPL = 0 then the value of ROA 39,702%, then when the number of NPL up 1%, ROA would decrease the amount of 1,468%. Pearson product moment correlation coefficient of -0.842 that meant NPL and ROA showed a very strong relationship and in the opposite direction, the coefficient of determination 70,80% and the remaining of 29.20% was influenced by other factors which were not examined by the writer. While hypothesis test showed tcount: -2.699 < ttabel: 3.182, which meant that a not significant and negative influenced Return On Assets. The suggestions to overcome the problems are that, the bank should have a special staff to supervise non-performing loans, and then fix the application of credit application such as listing the points the business targets for the next 6 months, and the bank should reinforce the management team of risk that problems related to NPL that can be minimized in the future.